The importance of frequent follow-up in the first year after pacemaker implantation upon detection of atrial tachyarrhythmia - Nowek, Anna; Chudzik, Michał; Wranicz, Jerzy K. (Medical Studies/Studia Medyczne, 2016)
Introduction: Newer pacemakers have data storage capabilities that permit detection of multiple episodes of atrial tachyarrhythmias (AT). Aim of the research : To document the frequency, time to first AT detection after implantation, and risk factors for symptomatic episodes and to determine the prevalence and predictors of pacemaker-detected AT. Material and methods: Patients (n = 62), from a single centre, with an implanted pacemaker that automatically recorded the cumulative daily AT burden were included in the analysis. The clinical history regarding AT was collected before implantation. Follow-ups were done at 3, 6, and 12 months after implantation with interrogation and symptoms reported from patients. Echocardiography was performed at baseline and at 12 months. Results: Atrial tachyarrhythmia was detected by the pacemaker in 16 (25.81%) of 62 patients. AT/atrial fibrillation (AF) burden was detected after 3 months in 13 out of 16 (81.25%) patients, and in 38.46% of them there was no clinical history of AF. Asymptomatic episodes occurred in 7 patients (43.75% – 3 men and 4 women), and 2 (28.57%) of them did not have a clinical history of AF. History of AF prior to implantation was significant for the appearance of AT/AF burden (p = 0.006), and use of β-blockers significantly limited AT/AF burden (p = 0.040). Other analysed data was statistically non-significant. Conclusions: Pacemaker-detection of AT is often the first paroxysmal AT diagnosis in asymptomatic patients. This suggests that AT data, collected from capable pacemakers and frequently reviewed, can lead to new diagnosis and early treatment in that group of patients, which could influence mortality and morbidity.